2011
DOI: 10.1161/circulationaha.111.048934
|View full text |Cite
|
Sign up to set email alerts
|

COP9 Signalosome Regulates Autophagosome Maturation

Abstract: Background Autophagy is essential to intracellular homeostasis and involved in the pathophysiology of a variety of diseases. Mechanisms regulating selective autophagy remain poorly understood. The COP9 signalosome (CSN) is a conserved protein complex consisting of 8 subunits (CSN1 through CSN8) and known to regulate the ubiquitin-proteasome system (UPS). However, it is unknown whether CSN plays a role in autophagy. Methods and Results Marked increases in LC3-II and p62 proteins were observed upon Csn8 deplet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
106
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(114 citation statements)
references
References 24 publications
7
106
0
Order By: Relevance
“…These results argue against the possibility that accumulation of AVs and ubiquitinated protein aggregates stems from a failure of autophagosome removal due to impaired lysosome biogenesis or autophagosome maturation, the disruption of which has been linked to cell death (42). Together, these findings indicate that coadministration of a Cdk inhibitor with an autophagy-inducing BH3 mimetic triggers inefficient autophagy characterized by an impaired ability of cells to clear ubiquitinated, malfolded proteins.…”
Section: Resultsmentioning
confidence: 93%
“…These results argue against the possibility that accumulation of AVs and ubiquitinated protein aggregates stems from a failure of autophagosome removal due to impaired lysosome biogenesis or autophagosome maturation, the disruption of which has been linked to cell death (42). Together, these findings indicate that coadministration of a Cdk inhibitor with an autophagy-inducing BH3 mimetic triggers inefficient autophagy characterized by an impaired ability of cells to clear ubiquitinated, malfolded proteins.…”
Section: Resultsmentioning
confidence: 93%
“…Our results indicate that CSN1 does not cooperate with IFT20 in the regulation of TCR trafficking to the IS but do not rule out a role for this protein in signalling events downstream of TCR stimulation. Recent evidence has implicated the COP9 signalosome in another critical quality control pathway, namely, autophagy (Pearce et al, 2009;Su et al, 2011;Zhang et al, 2016). Remarkably, the IFT system has been shown to participate in the first steps of autophagosome formation in ciliated cells (Pampliega et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Besides the fact that immunity and SA responses are affected in csn3, csn4, and csn5 mutants, the COP9/signalosome (CSN) complex modulates protein degradation in eukaryotes by regulating the ubiquitin-proteasome system. It was shown in mice that the COP9 signalosome regulates autophagosome maturation (Su et al, 2011). The authors observed the accumulation of immature autophagosomes in csn8 mouse cardiomyocytes.…”
Section: Why Do Autophagy Mutants Overexpress Defense Genes?mentioning
confidence: 97%